MICROBIOLOGICAL SPECTRUM OF THE GINGIVAL SULCUS IN SUBJECTS WITH CHRONIC CATARRHAL GINGIVITIS - Kotelban Andrii Yuriiovych; Luchynskiy Mykhailo Antonovych; Luchynskiy Vitaliy Mykhailovych; Rozhko Vitaliy Ivanovych; Basista Anastasiia Stepanivna (Research Retrieval and Academic Letters, 2024)
The article presents the results of clinical and microbiological studies in young people with chronic catarrhal gingivitis. Imbalance of oral cavity microflora becomes an important factor in the development of periodontal diseases. In the oral cavity, and especially in the affected periodontal tissues, are ideal conditions for the development and reproduction of microorganisms. The aim of the study was to study the microbiological spectrum of the gingival sulcus in subjects with chronic catarrhal gingivitis and to determine the sensitivity of St. and Str. to the most commonly used antibiotics in dentistry.